Spectral–time analysis of cycle fluctuations in lake water levels in Belarus and Poland - Volchak Alexander A.; Kirvel Ivan; Choiński Adam; Parfomuk Sergey I.; Kirvel Pavel; Sidak S. (Limnological Review, 2020)
On the basis of the mean volume of annual water levels of 25 lakes (9 Belarusian and 16 Polish) over a period of 55 years (1956-2010) spectral time analysis of water fluctuations has been executed. The choice of the lakes was based on two factors, i.e. the continuous period of observation and insignificant anthropogenic influence. The complex analysis of water level fluctuation cycles has shown that for Belarus the cycles observed most often were 3, 5 and 10-year cycles. Polish lakes also have three cycles, but in the majority of them they amount to 5 and 10-years. It can be assumed that this is impacted by the continental climate growing to the east. Most probably it is one of the key factors defining the diversity of water fluctuations in all the analyzed lakes.